2022
DOI: 10.1111/1750-3841.16100
|View full text |Cite
|
Sign up to set email alerts
|

Germinated chickpea–maize extrudates with high protein content and reduced starch digestibility

Abstract: The objective of this study was to produce maize extrudates supplemented with germinated chickpea flour to increase the contents of resistant starch (RS) and protein. Six extrudates were formulated using maize grits (ME), germinated chickpea flour (GCE) and different blends of maize and 10%, 20%, 30%, or 40% of germinated chickpea flour (MGCE‐10, MGCE‐20, MGCE‐30, or MGCE‐40). Increase of RS was observed in the defatted samples due to germinated chickpea flour addition. In the nondefatted samples, the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…One such effort is the blending of wheat flour (WF) with non‐WFs, having requisite nutritional and functional properties for improved bread quality (Guardianelli et al., 2019), and germinated legumes could be considered. Some studies have reported the use of germinated legumes, wholly or partially substituted with cereal flours, in product development (Chinma, Adedeji, et al., 2021; Millar, Barry‐Ryan, et al., 2019; Polat et al., 2020; Serrano‐Sandoval et al., 2022). Moreover, more studies are required to exploit more germinated legumes in food processing.…”
Section: Introductionmentioning
confidence: 99%
“…One such effort is the blending of wheat flour (WF) with non‐WFs, having requisite nutritional and functional properties for improved bread quality (Guardianelli et al., 2019), and germinated legumes could be considered. Some studies have reported the use of germinated legumes, wholly or partially substituted with cereal flours, in product development (Chinma, Adedeji, et al., 2021; Millar, Barry‐Ryan, et al., 2019; Polat et al., 2020; Serrano‐Sandoval et al., 2022). Moreover, more studies are required to exploit more germinated legumes in food processing.…”
Section: Introductionmentioning
confidence: 99%
“…The infrared spectra of NRS and extrudates are shown in Figure 7. For NRS, the bands between 800 and 1200 cm −1 are the characteristic fingerprint region for starch, the bands between 990 and 1000 cm −1 are the stretch vibration region for C‐O, and the bands between 1075 and 1080 cm −1 and 1145 and 1150 cm −1 are the C‐OH skeletal vibration and asymmetric binding (Serrano‐Sandoval et al., 2022). For protein samples, the bands in the range of 1580–1720 cm −1 and 1480–1580 cm −1 are the characteristic peaks of the amide I band and the amide II band, respectively (Lu et al., 2016).…”
Section: Resultsmentioning
confidence: 99%